EXAMINING THE DEMAND RELATIONSHIPS OF BETWEEN RELIGIOUS TOURISM AND EXAMPLE OF URBAN ATTRACTIONS IN THE GYŐR-PANNONHALMA TOURIST AREA - Ferenc DARABOS; Csaba KŐMÍVES; Kevser ÇINAR; Anne-Marie LEBRUN (Geo Journal of Tourism and Geosites)
This study examines the sacred places of Győr-Moson-Sopron County (Western Hungary), focusing on people's attitudes towards them. Pannonhalma is part of the world heritage, the Győr Cathedral, and the five church festivals (Roman Catholic, Jewish, Reformed, Lutheran, Greek Oriental) held in the city are important places of worship. The aim of the study was to analyse the scope of religious tourism in the World Heritage Site and to examine the demographics of the demand for urban religious centres. Primary research was conducted with a quantitative (questionnaire) survey between 10th September 2023 and 30th October 2023. The sample of 666 persons is not representative, respondents were chosen with arbitrary sampling. Data were processed using the SPSS 23 statistical program package which contains cross-table analysis, in addition to the descriptive statistical analyses. The most important finding of the study is that travel propensity is determined by the importance and familiarity of urban landmarks, and significance can be found here. Respondents' age, educational attainment and gender also show significant differences in terms of the attractiveness of visiting attractions (distance from their residence). The research investigated the demand for Roman Catholic, Jewish, Reformed, Evangelical and Greek Orthodox religious attractions in Győr and the Pannonhalma Benedictine Abbey, a World Heritage Site, according to local specificity. There is significant evidence of a regional pull effect of the World Heritage status of the built heritage site. The city churches and their associated events are most popular with the elderly, women and those with higher education.